On the discovery of ferromanganese nodules in the World Ocean. (September 2021) - Belkin, Igor M.; Andersson, Per S.; Langhof, Jörgen
Abstract: For a century, the discovery of ferromanganese (Fe–Mn) nodules in the World Ocean was universally and indisputably credited to the Challenger circum-global oceanographic expedition of 1872–1876, during which the first manganese nodules and crusts were dredged up from the sea floor in February–March 1873. A century later, a counterclaim appeared in the literature, crediting Nordenskiöld's expedition on Sofia in 1868, five years before the Challenger findings, for the discovery of Fe–Mn nodules in the ocean. This counterclaim, widely accepted without scrutiny, was based on the Gustaf Lindström (1884) chemical analysis of a single bottom sediment sample among 14 samples from two Arctic expeditions led by Nordenskiöld: Sofia 1868 and Vega 1878–1880. The Lindström (1884) report published as an eight-page brochure in Swedish remained almost unknown to the research community until now. A close examination of this report and other historical evidence revealed that the counterclaim of discovery by the Sofia 1868 expedition to the Kara Sea is invalid based on three notable facts: (1) Sofia never sailed in the Kara Sea; (2) the single bottom sediment sample with an extremely high content of Mn (24%), was collected in the Kara Sea during the Vega Expedition across the Northeast Passage; (3) the Vega sampling was in 1878, not in 1868. Meanwhile, five and a half years prior to the Vega sampling, the first Fe–Mn nodules and crusts were dredged up from the sea floor on 18 February and March 7, 1873 during the Challenger expedition. These findings have been promptly reported and published in May 1873. Thus, the credit for the discovery of ferromanganese nodules in the World Ocean firmly belongs to the Challenger expedition. Highlights: The discovery of ferromanganese nodules in the World Ocean is revisited. The Lindström (1884) paper with chemical analyses of sediment samples from Nordeskiöld's expeditions is examined . The discovery of ferromanganese nodules in the World Oceanduring the Challenger 1872–1876 expedition is confirmed.